Hayat dışı sigorta şirketlerinin vergilendirilmesi ve örnek uygulama - Tüleylioğlu, İbrahim (My University, 2007)
HAYAT DIŞI SİGORTA ŞİRKETLERİNİN VERGİLENDİRİLMESİ VE ÖRNEK UYGULAMA Ekonominin en önemli sektörlerinden olan Sigorta Sektörü son yıllarda gerek Avrupa Birligi uyum çalısmaları gerekse teknolojik yenilikler ve halkın bilinçlenmesi sonucu önemini arttırmıstır.Sigorta Sektörünün öneminin hiç süphesiz ekonomik bir karsılıgı olacaktır.Bu karsılıkta vergi’dir. Bu çalısmada Genel Vergi Teorisi ve Sigorta Sektörün de yer alan kisi ve kurumlar dahilinde Sigorta Sirketlerinin Vergilendirilmesi incelenmistir. Vergi kamu maliyesinin en önemli gelir kaynagıdır.Dolayısıyla vergi hem devleti hem de verginin sorumlusu olan tüm kisi ve kurumları ilgilendirir.Çalısmamızda vergi teorisi tüm yönleriyle incelenmistir.Çalısmanın bütünlügü açısından Genel Vergi Teorisi incelenerek konunun daha iyi anlasılması için baslangıç yapılmıstır. Sigorta Sektörü’nde yer alan tüm kisi ve kurumlar gerek hukuki statü gerek vergisel açıdan degerlendirilmistir.Sektörde yer alan kisi ve kurumlar tek tek ele alınarak konunun bütünlügüne destek verilmesi amaçlanmıstır.Sektörde yer alan kurum ve kisiler incelendikten sonra sektörün temel tası olan Sigorta Sirketleri incelenmistir.Sigorta Sirketleri tüm vergi bransları açısından ayrıntılı olarak degerlendirilmistir. Çalısmamızın sonunda örnek bir vergi uygulaması yer almaktadır.Ayrıntılı olarak anlatılan konu örnek uygulama ile sonuçlandırılmıstır

TAXATION OF NON-LIFE INSURANCE COMPANIES AND SAMPLE APPLICATION Insurance sector, as one of the most important sectors of the economy, has increased it’s importance during the recent years in the result of European Union harmonization code and technological novelties as well as the awareness of the people. Without doubt, there will be the economical return of Insurance Sector’s importance. In this study, the Taxation of the Insurance Companies has been examined within General Tax Theory with the persons and establishments taking place in it. Tax is the most important source of income for the public finances. Consequently, tax concern both all of the persons and the establishments who are responsible for it. In our study, the Tax Thehory has been examined in all it’s bearings. For the integrity of the study, General Tax Theory is examined and the initializing of the subject has been made for the better understanding of the topic. All of the persons and establishments taking place in the Insurance Sector have been evaluated as regards to their legal states and with the texation point of view as well. The persons and establishments taking place in the sector have been handled one by one and the support for the integrity of the topic has been aimed. After having the evaluations of the persons and establishments taking place in the sector, the Insurance Companies have been evaluated as the basic element of the sector. Insurance Companies have been evaluated with full details as regards to all tax branches. In the conclusion of our study, a sample tax application takes place. The topic has been narrated in full details and it has been concluded with the sample application
Keywords: Bankalar ve Bankacılık; Sigortacılık; Vergilendirme; Vergilendirme_Sigortacılık